Betrothal or breakaway eaudiobook - Brunner, Leah (D.C. Eagles Hockey, 2024)
Book three in the wildly popular D.C. Eagles Hockey Series! Can Ford Remington—team captain of the D.C. Eagles—forge the future he wants? Ford's love life isn't non-existent, it's just hopelessly one-sided. And the only woman he's ever wanted—his childhood best friend, Amber—doesn't reciprocate his feelings. So why bother dating? When Amber's fiancé leaves her pregnant without health insurance, she's prepared to do it all alone—until childbirth causes complications with her heart and she needs minor heart surgery. Ford proposes a plan: a quickie wedding, insurance for Amber and her baby girl, and two years of platonically wedded bliss. But how will he let go when he's not only in love with Amber but also with her baby girl who now feels like his own? And even worse, Ford might have to walk away sooner than he ever expected... Betrothal or Breakaway is a dual POV, fade to black romance with lots of sizzle, but no spice. This work of fiction contains mild language, depictions of child neglect, bullying (minimal), and the death of an animal (not descriptive). If you are sensitive to these subjects, please use these trigger warnings to make an informed decision about listening to this audiobook.